Perspectives of European Patient Advocacy Groups on Volunteer Registries and Vaccine Trials: VACCELERATE Survey Study - Sophia Themistocleous; Christos D Argyropoulos; Paris Vogazianos; George Shiamakkides; Evgenia Noula; Andria Nearchou; Andreas Yiallouris; Charalampos Filippou; Fiona A Stewart; Markela Koniordou; Ioannis Kopsidas; Helena H Askling; et al. (JMIR Publications, 2024)
BackgroundThe VACCELERATE Pan-European Scientific network aims to strengthen the foundation of vaccine trial research across Europe by following the principles of equity, inclusion, and diversity. The VACCELERATE Volunteer Registry network provides access to vaccine trial sites across the European region and supports a sustainable volunteer platform for identifying potential participants for forthcoming vaccine clinical research. ObjectiveThe aim of this study was to approach members of patient advocacy groups (PAGs) across Europe to assess their willingness to register for the VACCELERATE Volunteer Registry and their perspectives related to participating in vaccine trials. MethodsIn an effort to understand how to increase recruitment for the VACCELERATE Volunteer Registry, a standardized survey was developed in English and translated into 8 different languages (Dutch, English, French, German, Greek, Italian, Spanish, and Swedish) by the respective National Coordinator team. The online, anonymous survey was circulated, from March 2022 to May 2022, to PAGs across 10 European countries (Belgium, Cyprus, Denmark, France, Germany, Greece, Ireland, Italy, Spain, and Sweden) to share with their members. The questionnaire constituted of multiple choice and open-ended questions evaluating information regarding participants' perceptions on participating in vaccine trials and their willingness to become involved in the VACCELERATE Volunteer Registry. ResultsIn total, 520 responses were collected and analyzed. The PAG members reported that the principal criteria influencing their decision to participate in clinical trials overall are (1) the risks involved, (2) the benefits that will be gained from their potential participation, and (3) the quality and quantity of information provided regarding the trial. The survey revealed that, out of the 520 respondents, 133 individuals across all age groups were "positive" toward registering in the VACCELERATE Volunteer Registry, with an additional 47 individuals reporting being "very positive." Respondents from Northern European countries were 1.725 (95% CI 1.206-2.468) times more likely to be willing to participate in the VACCELERATE Volunteer Registry than respondents from Southern European countries. ConclusionsFactors discouraging participants from joining vaccine trial registries or clinical trials primarily include concerns of the safety of novel vaccines and a lack of trust in those involved in vaccine development. These outcomes aid in identifying issues and setbacks in present registries, providing the VACCELERATE network with feedback on how to potentially increase participation and enrollment in trials across Europe. Development of European health communication strategies among diverse public communities, especially via PAGs, is the key for increasing patients' willingness to participate in clinical studies.